Pelaksanaan Bauran Pemasaran Ayam Geprek Juara Cabang Kota Banjar - Nabila Iasha; Annisa Desty Puspatriani; Arip Budiman (EKOBIMA, 2023)
The marketing mix strategy is the foundation and the main capital for a business to achieve the goals it wants. In the marketing mix, there are at least 4P that must be considered, namely product, price, place/location, and promotion. The purpose of this Final Project is to find out the implementation of the marketing mix that is carried out by Ayam Geprek Champion, Banjar City Branch. The research method used is descriptive method with a qualitative research approach, in which the author describes the results of observations and analyzes the data obtained in the field. After conducting analysis and discussion of the problem, the authors concluded that the implementation of the marketing mix at Ayam Geprek Champion Branch in Banjar City was going well, but it had not been implemented properly because there were still some problems in its implementation